2023
DOI: 10.2514/1.j062783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shock Waves on Shack–Hartmann Wavefront Sensor Data

Abstract: Shock waves will form by turning supersonic or locally supersonic flow and result in an increase in the freestream density downstream of the shock. This increase leads to optical distortions that limit the effectiveness of aircraft-mounted laser systems. In this paper, analytic expressions are developed to describe these optical distortions in terms of the optical-path difference (OPD). Pupil-plane disturbances imposed by the shock are studied for two cases: when the shock is parallel to the propagation direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 23 publications
3
43
0
Order By: Relevance
“…After creating a complex-optical field with an optical-vortex-phase function, the complex-optical field is applied to a SHWFS model, similar to the ones used in Refs. [27,32,40,41]. The resultant SHWFS image can be seen in the top-right plot of Fig.…”
Section: Simple Optical-vortex Modelmentioning
confidence: 97%
“…After creating a complex-optical field with an optical-vortex-phase function, the complex-optical field is applied to a SHWFS model, similar to the ones used in Refs. [27,32,40,41]. The resultant SHWFS image can be seen in the top-right plot of Fig.…”
Section: Simple Optical-vortex Modelmentioning
confidence: 97%
“…16 However, when there is a discontinuity across the lenslet, the irradiance pattern bifurcates or smears, and C-tilt is no longer a good estimate of G-tilt. 7 Since the wavefront is constructed through a least-squares reconstructor, these contaminated tilt measurements affect the accuracy of the entire reconstructed wavefront.…”
Section: Procedures For Calculating Higher-order Momentsmentioning
confidence: 99%
“…[2][3][4][5] A large interest is in higher speed transonic and supersonic flow regimes, where shocks can form a sharp change in density, thereby affecting the index of refraction and having a significant effect on beam propagation. Kalensky et al 6,7 have shown that the presence of the shock will deteriorate the performance of SHWFS. As a reminder, SHWFS is comprised of an array of subaperture lenslets focused onto a camera sensor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations